Improved Rijndael Algorithm by Encryption S-Box Using NTRU Algorithm - H. Mahmoud, Halah; M.Hoobi, Mayes (Iraqi Journal of Science, 2023)
With the wide developments of computer science and applications of networks, the security of information must be increased and make it more complex. The most important issues is how to control and prevent unauthorized access to secure information, therefore this paper presents a combination of two efficient encryption algorithms to satisfy the purpose of information security by adding a new level of encryption in Rijndael-AES algorithm. This paper presents a proposed Rijndael encryption and decryption process with NTRU algorithm, Rijndael algorithm is important because of its strong encryption. The proposed updates are represented by encryption and decryption Rijndael S-Box using NTRU algorithm. These modifications enhance the degree of complexity, increase key search space, and make the ciphered message difficult to be cracked by the attacker.